Implementation of an event-triggered smart sensor network architecture based on the IEEE 802.15.4 standard - Erico Meneses Leão (2007)
A smart transducer is the integration of a sensor/actuator element, a processing unit, and a network interface. Smart sensor networks are composed of smart transducer nodes interconnected through a communication network. This paper presents an event driven smart sensor network architecture (asynchronous data) and its respective implementation based in the IEEE 802.15.4 standard. The events are derived from a data compression algorithm embedded into the smart sensor, which compresses data from the sensor. The architecture also supports configuration and monitoring activities for the over all distributed system.